The Impact of Experiential Learning on Student’s Knowledge - ‘Aini, Shinta Futichatul; Arumsari, Nanda Zeni; Sari, Hani Fitria; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
The purpose of this study is to find out how the influence of the use of experiential learning models as a means of increasing student’s knowledge in the Covid-19 pandemic. This research uses Class Action Research (PTK) with a quantitative approach. The subjects in the study were 5th graders totaling 22 children. But the authors only sampled 10 children due to the current pandemic situation, which does not allow the authors to gather all the children in one class. Authors use essay tests to measure students' abilities. The average Cycle 1 score that students get is 71.5 and the average Cycle 2 score that students get is 86.5. There is a significant increase in value after and before the study using experiential learning models. The results of this study show that the Experiential Learning model has a positive effect on student’s knowledge.